Evaluation of maternal near miss cases in tertiary care centre - Vandana Ojha; Amrita Chaurasia; Shalini Singh; Nidhi Sachan; Shadma Siddiqui (Barpeta Obstetrics and Gynaecological Society, 2019)
Objective: A study to analyze maternal near miss obstetrics event and maternal mortality in a tertiary care centre. Methods: This was a retrospective analysis of data, from January 2015 to December 2017. For each eligible patient, medical records were reviewed. Their socio-demographic features, mode of delivery, diagnosis on admission, surgical intervention, ICU admission, duration of hospital stay and outcome were collected and analyzed. Results: There were 159 maternal near miss cases and 83 maternal deaths. Maternal near miss to mortality ratio was 1.92. During the study maternal near miss incidence (MNM ratio) was found to be 47. 73 per 1000 live birth. Mortality index in our study was 34.29. There was more than one delay in most of the patients. Delays were primarily in seeking health care and delayed referral. Haemorrhage, hypertensive disorders and rupture uterus are most common cause of maternal near miss in our study. Conclusion: Investigating the maternal near miss cases are important tool to get the information about the causes, identify the gaps and corrective measures to be taken in the health care system.